Integrated Stress Response Triggered by Excessive Glycosylation Drives Thoracic Aortic aneurysm - Rochano Ortiz, Antonio; San Sebastian Jaraba, Irene; Zamora, Carmen; Simó, Carolina; García Cañas, Virginia; Martínez Albaladejo, Sacramento; Fernandez Gomez, María José; Velho, Tiago R.; Ruíz Rodríguez, María Jesús; Leal Zafra, Amanda; Gabandé, Enrique; Martinez Martinez, Sara; et al. (bioRxiv, 2024)
Thoracic aortic aneurysms and dissections (TAAD) are marked by degenerative changes in the aortic media. Marfan syndrome is the most common inherited connective tissue disorder associated with TAAD. While vascular smooth muscle cell (VSMC) metabolism is emerging as a targetable driver of aortic aneurysm, surgical interventions remain the primary strategy to prevent aortic dissection. Our research indicates that the hexosamine biosynthetic pathway (HBP), a branch of glycolysis, is upregulated in aortas from the Fbn1C1041G/+ Marfan Syndrome mouse model. Enhancing HBP activity promotes aortic dilation and accumulation glycan-rich extracellular matrix, contributing to aortic medial degeneration in wild-type mice. Mechanistically, fueling HBP activity induces VSMC dysfunction through excessive glycosylation, which activates the Integrated Stress Response (ISR). Pharmacological inhibition of HBP, along with ISR inhibition, successfully reverses aortic dilation and aortic medial degeneration in Fbn1C1041G/+ Marfan Syndrome mouse model. Additionally, Marfan Syndrome patients show elevated levels of HBP metabolites in blood plasma and serum, and heightened HBP-ISR signaling in patients with TAAD. These findings unveil a potential causative role for the HBP-ISR axis in medial degeneration in human TAAD, underscoring the need for evaluating HBP and ISR pathway as novel biomarkers and therapeutic strategies for thoracic aortic aneurysm.